Between the Stationary and the Mobile: Rural Library Spaces and Activities in Soviet Lithuania (1959–1987) - Suchodolskytė, Agnė (Knygotyra, 2025)
This article examines the spatial and functional transformations of rural libraries in Soviet Lithuania during the period from 1959 to 1987. Libraries are analysed not only as brick-and-mortar institutions, but also as evolving spatial and social practices that transcend the traditional concept of the library. The study seeks to reveal how they functioned not merely as tools of ideological control, but also as important cultural centres whose activities extended far beyond their premises. Emphasis is placed on the creation of expanded library spaces that encompassed reading, as well as broader social and cultural interaction. To trace these practices, the study draws on archival sources from the districts of Ukmergė, Širvintos, Švenčionys and Trakai – including annual reports, correspondence, and activity plans. It explores how libraries functioned in unsuitable premises, often lacking adequate infrastructure and resources. Despite such constraints, they organised events in schools, cultural centres, and collective farms, delivered literature to readers, and carried out mobile outreach activities. The distribution of books was also supported by the so-called ‘book carriers’ (in Lithuanian: knygnešiai), who were contributors delivering books to readers so that to fulfil the readership targets imposed from above. Mobility became an integral part of the library work, driven by practical limitations and the need to reach communities through various means. These findings offer a renewed perspective on the role of libraries in the everyday life of Soviet rural society.